Tónlistarhúsið Harpa - nýtt kennileiti og aðdráttarafl ferðamanna - Inga Hrund Magnúsdóttir 1988- (2012)
In May 2011 the Reykjavík concert hall and conference centre Harpa was officially opened for the public and some believe she is the goal to success for increasing foreign tourists to Iceland outside the high season. Both by holding concerts and conferences as well as serving as a landmark feature for Reykjavík. The aim of this thesis is to examine the expectations towards Harpa on tourism, especially on low season tourism in Reykjavík and the emphasis made in marketing of the house. A qualitative method was used and six interviews taken. Three of the informants work for Harpa and the other three work in the tourism sector and have a strong opinion towards the new house Harpa. The results showed that the interviewees agreed on that Harpa would have a positive affect on low season in tourism in Reykjavík since the house is fully booked for the next few years. Some internationally well known artists have already performed in Harpa and attracted many foreign tourists. Harpa has an affect on tourism businesses since these guests used other services during their stay in Reykjavík such as accommodation. Harpa has been marketed itself abroad through a company in New York as well as in London and has got positive reviews in magazines and newspapers. Harpa is a house for all people and it belongs to everybody and therefore the future is bright according to the people interviewed. Í maí 2011 var Harpa tónlistar- og ráðstefnuhús Íslendinga formlega opnuð og binda margir vonir um það að hún sé lykillinn til þess að laða að ferðamenn utan háanna tíma í ferðaþjónustu, bæði með tónlistar- og ráðstefnuhaldi ásamt því að þjóna sem kennileiti og aðdráttarafl Reykjavíkurborgar. Markmið þessarar rannsóknar er að kanna væntingar til áhrifa Hörpu á ferðaþjónustu þá sérstaklega á lágannatíma í Reykjavík og hverjar áherslur eru í markaðssetningu hjá þessum nýja aðila á markaðinum. Við gagnaöflun var notast við eigindlegar rannsóknaraðferðir og tekin viðtöl við þrjá aðila sem starfa í Hörpu ásamt þremur ferðaþjónustuaðilum sem hafa ...